The effect of phase front deformation on the growth of the filamentation instability in laser-plasma interactions - Higson, E; Trines, R; Jiang, J; Bingham, R; Lancaster, K; Davies, JR; Norreys, P (2013)
Laser pulses of 0.9 kJ/1 ns/1053 nm were focused onto low-Z plastic targets in both spherical and planar geometry. The uniformity of the resulting plasma production was studied using x-ray pinhole imaging. Evidence is provided suggesting that thermal filamentation starts to occur for irradiances on the target of Iλ2 1014 W cm-2 μm 2, even on deployment of phase plates to improve the focal spot spatial uniformity. The experiments are supported by both analytical modelling and two-dimensional particle-in-cell simulations. The implications for the applications of laser-plasma interactions that require high degrees of uniform irradiation are discussed. © IOP Publishing and Deutsche Physikalische Gesellschaft.